UJI AKTIVITAS ANTI BAKTERI MADU TRIGONA TERHADAP BAKTERI Escherichia coli dan Klebsiella pneumoniae - Gultom, Endang Sulistyarini; Pohan, Selvia Dewi; Situmorang, Nurbaity; Hafzari, Rini (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2025)
Antibiotic resistance has the greatest impact on human health, at least 2 million people are infected by antibiotic-resistant bacteria. The use of natural medicines is increasingly in demand by the public, one of which is often used to treat diseases is trigona honey. This study aims to determine the antibacterial activity of Trigona honey against Escherichia coli and Klebsiella pneumoniae bacteria. The test bacteria used were Multidrug Resistant Escherichia coli and Klebsiella pneumoniae bacteria obtained from the collection of the Microbiology Laboratory of the University of North Sumatera Hospital. Antimicrobial activity testing was carried out using the hole / well diffusion method on Mueller Hinton Agar (MHA) media with chloramphenicol as a positive control, acetone as a negative control and trigona honey with a concentration of 500 ppm. Antibacterial activity was seen by measuring the inhibition zone formed. The results showed that Trigona honey was able to inhibit the growth of Escherichia coli and Klebsiella pneumoniae bacteria with inhibition zone activity included in the weak category, while the positive control showed antibacterial activity in the strong category.